The Difference in Green Bean Flour Substitution on Organoleptic Quality, Preference, and Protein Content in Semprong Cake - Natalia, Yohana Margareta; Suryatna, Bambang Sugeng (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2023)
Abstract : Semprong cake is a traditional Indonesian cake made from rice flour, coconut milk, eggs, sugar, salt, margarine and vanilla with processing techniques baked using a semprong mold and then rolled to resemble an egg roll, triangular, flat like a fan and rectangular. Various kinds of semprong cakes can easily be obtained in modern markets and traditional markets. The characteristics of a semprong cake, namely crunchy, sweet and savory, make many people like semprong cakes. Semprong cake has experienced diversification of flavors, but not much has been developed in the diversification of the basic ingredients of semprong cake. In this study, researchers used green beans as a substitute for mung bean flour in making semprong cakes so that they could produce healthy and nutritious traditional snacks. The substitution material for semprong cake in this study was mung bean flour with different compositions, namely 0%, 40%, 50%, and 60%. The reason underlying the researchers chose mung beans as a substitute for mung bean flour for making semprong cakes was in terms of the availability of mung bean raw materials, which are ingredients that are easy to find in the market, have complete nutritional content, have good benefits for health and are liked by the community. Research objectives: (1) To find out the differences in the use of mung bean flour substitute ingredients 0%, 40%, 50%, 60% on the organoletic quality of semprong cakes in terms of color, texture, aroma, and taste, (2) To find out the level of public preference on green bean flour substitute semprong cake 0%, 40%, 50%, 60% in terms of color, aroma, texture, and taste, (3) To determine the nutritional content of green bean flour substitution semprong cake protein 0%, 40%, 50 %, 60%. Keywords: Semprong Cake, Mung Bean Flour Substitution, Organoleptic Quality Abstrak : Kue semprong adalah kue tradisional Indonesia yang terbuat dari tepung beras, santan, telur, gula, garam, margarine dan vanili dengan teknik pengolahan di panggang menggunakan cetakan semprong kemudian digulung menyerupai egg roll, segitiga, pipih seperti kipas dan persegi panjang. Beraneka ragam kue semprong dengan mudah dapat diperoleh di pasar modern maupun pasar tradisional. Karakteristik dari kue semprong yaitu renyah, manis dan gurih membuat banyak masyarakat menyukai kue semprong. Kue semprong telah mengalami diversifikasi varian rasa namun belum banyak berkembang diversifikasi bahan dasar kue semprong. Pada penelitian ini peneliti memanfaatkan kacang hijau sebagai bahan substitusi tepung kacang hijau pada pembuatan kue semprong sehingga dapat menghasilkan kudapan tradisional yang sehat dan bergizi. Bahan substitusi kue semprong pada penelitian ini adalah substitusi tepung kacang hijau dengan komposisi berbeda yaitu 0%, 40%, 50%, dan 60%. Alasan yang mendasari peneliti memilih kacang hijau sebagai bahan substitusi tepung kacang hijau pembuatan kue semprong yaitu ditinjau dari ketersediaan bahan baku kacang hijau yaitu bahan mudah ditemukan dipasaran, kandungan gizi yang lengkap, memiliki manfaat yang baik bagi kesehatan dan di sukai masyarakat. Tujuan penelitian : (1) Untuk mengetahui perbedaan penggunaan bahan substitusi tepung kacang hijau 0%, 40%, 50%, 60% terhadap kualitas organoletik kue semprong dari segi warna, tekstur, aroma, dan rasa, (2) Untuk mengetahui tingkat kesukaan masyarakat terhadap kue semprong substitusi tepung kacang hijau 0%, 40%, 50%, 60% dari segi warna, aroma, tekstur, dan rasa, (3) Untuk mengetahui kandungan gizi protein kue semprong substitusi tepung kacang hijau 0%, 40%, 50%, 60%. Kata kunci : Kue Semprong, Substitusi Tepung Kacang Hijau, Kualitas Organoleptik